Intercultural Communication: A Study on Music as an Element in the Wayang Kulit of Kelantan - Eyo Leng Yan,; Rosdeen Suboh,; Marzelan Salleh, (Wacana Seni Journal of Arts Discourse, 2021)
This research discusses intercultural relations in the performing art of wayang kulit Kelantan, by examining the phenomena of communication between cultures that occur within the multi-ethnic Kelantanese community, with a focus on the element of music. In order to understand the intercultural communication that occurs in the element of music, Kumpulan Wayang Kulit Sri Campuran was chosen as the main research subject due to the group’s characteristic ethnic diversity, which comprises Malay, Chinese, and Siamese, as well as the community that is directly and indirectly involved in the performance, which also comprises various ethnicities, thus illustrating the existence of the phenomena of intercultural communication. Methods of observation on the element of music in performances held at several locations by this group have been able to prove the existence of clear intercultural communications within the multi-ethnic community in Kelantan. These phenomena also show that this group specifically, and the Kelantanese community in general, upholds cultural collectivism that strengthens intercultural relations, whereby people from various cultural backgrounds can be brought together by a single performance that clearly showcases characteristics of teamwork, tolerance, understanding, compatibility, sharing, and harmony.Keywords:, ,,